Prevalence of diabetes mellitus and impaired glucose tolerance in factory workers from Transkei, South Africa - Erasmus, R T; Blanco Blanco, E; Okesina, A B; Matsha, T; Gqweta, Z; Mesa, J A (South African medical journal, 2001)
To determine the prevalence of diabetes mellitus and impaired glucose tolerance (IGT) in a group of peri-urban black South Africans. Cross-sectional study in which an oral glucose tolerance test (OGTT) was performed on each subject. Two of the largest factories in the surroundings of Umtata, the capital of the former homeland of Transkei, South Africa. A total of 374 Xhosa-speaking factory workers. Frequency of diabetes mellitus and IGT according to age group and gender using the current World Health Organisation (WHO) criteria for the diagnosis of abnormal glucose tolerance and its relationship to obesity. The crude prevalences for diabetes mellitus and IGT were 2.45% and 2.7% respectively. The age-adjusted prevalences using a standard world population were 4.5% (confidence interval (CI) 1.54-7.42) and 5.1% (CI 2.45-5.51) for diabetes and IGT respectively. The prevalence of diabetes was similar in male and female workers (P = 0.31), with the highest incidence observed in the age group from 40 to 59 years. No subject below the age of 40 years was found to be diabetic, and the prevalence of the disease was found to increase with age. Obesity was present in 22.2% of all subjects. Prevalence of obesity was similar in subjects with diabetes and in those with impaired and normal glucose tolerance (P = 0.71). However, overweight, identified in 26.8% of subjects, was more frequently observed in the IGT group than in the other two groups (P = 0.01). IGT was observed in 3.4% of male and 1.5% of female workers respectively (P = 0.13), with peak prevalences occurring between the ages of 30 and 49 years. In conclusion, this study found a prevalence of diabetes and IGT comparable to prevalence results reported in other black South African communities. The implications with regard to this community merit further study.